Applications of piggyBac Transposons for Genome Manipulation in Stem Cells - Yi Sun; Guang Liu; Yue Huang (Hindawi Limited, 2021)
Transposons are mobile genetic elements in the genome. The piggyBac (PB) transposon system is increasingly being used for stem cell research due to its high transposition efficiency and seamless excision capacity. Over the past few decades, forward genetic screens based on PB transposons have been successfully established to identify genes associated with drug resistance and stem cell-related characteristics. Moreover, PB transposon is regarded as a promising gene therapy vector and has been used in some clinically relevant stem cells. Here, we review the recent progress on the basic biology of PB, highlight its applications in current stem cell research, and discuss its advantages and challenges.